Vitamin D-Dependent Rickets: Eight Cases - Cesur, YAŞAR; CESUR, YAŞAR; Yuca, Sevil Ari; Bektas, Selcuk; Yilmaz, Cahide; Dulger, Haluk; Temel, Hayrettin (My University, 2016)
Objective: Vitamin D is essential for bone development and health, and deficiency resulting in rickets and skeletal deformities is seen mainly during rapid growth. Hereditary vitamin D dependent rickets type I and type II rickets is a very rare form of rickets, characterized by 1-alpha-hydroxylase deficiency or end-organ resistance to vitamin D. We aimed to investigate, clinical and laboratory characteristics of eight cases with Vitamin D-dependent rickets (VDRR). Method: The mean age of patients during diagnosis was 2.6 years. Excluding one patient, others were males (87.5%). Results: Mean laboratory values during referral was calcium 7.5 +/- 1,5 mg/dl, phosphorus 4 +/- 1.2 mg/dl, alkaline phosphatase (ALP) 1679 +/- 641 U/L and parathyroid hormone (PTH) 524 +/- 498 pg/ml. Patients received 1.2 mu g/kg/day calcitriol. During follow-ups serum ALP and PTH values of patients turned to normal levels. Conclusion: In rickets, cases with persistent increased serum ALP and PTH levels it will be appropriate to investigate serum 25 (OH) D levels in cases diagnosed with vitamin D-dependent rickets even though hypocalcaemia is absent. Administration of adequate doses of calcitriol in some cases is able to clinical and laboratory values return to normal.